KESALEHAN SOSIAL SISWA DALAM KEGIATAN JUM’AT TAKLIM DI MADRASAH IBTIDAIYAH RIYADUL FATHONAH CIKULUR LEBAK - Nuraeni, Fia; Budi, Asep; Nurhakim, Muhamad Syara; Taufiq (Ta'dibiya, 2025)
This study aims to determine the Implementation of Friday Taklim Activities in improving the Social Piety of Students at MI Riyadul Fathonah. The formulation of the problem in this study is: 1) How is the Implementation of Friday Taklim activities at MI Riyadul Fathonah? 2) What are the efforts and obstacles faced in implementing Friday Taklim activities at MI Riyadul Fathonah? 3) How can the implementation of Friday Taklim activities improve students' social piety? This study uses a Qualitative research method with a descriptive nature. Data collection techniques use observation, interviews and documentation, Data analysis techniques used in this study through three components, namely data reduction, data display and drawing conclusions. The results of this study can be described that Friday Taklim contributes to increasing social piety in its students, these contributions are: acting as an addition to religious knowledge in its students, namely: As an enhancer of religious knowledge such as prayer, reciting the Koran, fasting, and others. Improving children's skills, such as, actively praying in congregation at the Mosque, becoming an MC, a preacher, reading daily prayers, reading Juz Amma, some also read the Quran. As a place for community-based lifelong education. Keywords: Friday Taklim, Students' social piety